Antibody seroconversion in asymptomatic andsymptomatic patients infected with severe acuterespiratory syndrome coronavirus 2 (SARS-CoV-2) - Jiang, C; Wang, Y; Hu, M; Wen, L; Wen, C; Wang, Y; Zhu, W; Tai, S; Jiang, Z; Xiao, K; Faria, NR; De Clercq, E; et al. (Wiley, 2020)
Objectives Asymptomatic and symptomatic patients may transmit severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), but their clinical features and immune responses remain largely unclear. We aimed to characterise the clinical features and immune responses of asymptomatic and symptomatic patients infected with SARS‐CoV‐2. Methods We collected clinical, laboratory and epidemiological records of patients hospitalised in a coronavirus field hospital in Wuhan. We performed qualitative detection of anti‐SARS‐CoV‐2 immunoglobulin M (IgM) and immunoglobulin G (IgG) using archived blood samples. Results Of 214 patients with SARS‐CoV‐2, 26 (12%) were asymptomatic at hospital admission and during hospitalisation. Most asymptomatic patients were ≤ 60 years (96%) and females (65%) and had few comorbidities (< 16%). Serum levels of white and red blood cells were higher in asymptomatic than in symptomatic patients (P‐values < 0.05). During hospitalisation, IgG seroconversion was commonly observed in both asymptomatic and symptomatic patients (85% versus 94%, P‐value = 0.07); in contrast, IgM seroconversion was less common in asymptomatic than in symptomatic patients (31% versus 74%, P‐value < 0.001). The median time from the first virus‐positive screening to IgG or IgM seroconversion was significantly shorter in asymptomatic than in symptomatic patients (median: 7 versus 14 days, P‐value < 0.01). Furthermore, IgG/IgM seroconversion rates increased concomitantly with the clearance of SARS‐CoV‐2 in both asymptomatic and symptomatic patients. At the time of virus clearance, IgG/IgM titres and plasma neutralisation capacity were significantly lower in recovered asymptomatic than in recovered symptomatic patients (P‐values < 0.01). Conclusion Asymptomatic and symptomatic patients exhibited different kinetics of IgG/IgM responses to SARS‐CoV‐2. Asymptomatic patients may transmit SARS‐CoV‐2, highlighting the importance of early diagnosis and treatment.